Aphanius farsicus, a replacement name for A. persicus (Jenkins, 1910) (Teleostei, Cyprinodontidae) - Teimori, Azad; Esmaeili, Hamid Reza; Reichenbacher, Bettina (Zootaxa, 2011)
Gaudant (2011) has shown that Brachylebias Priem, 1908 is a junior synonym of Aphanius Nardo, 1827 and that therefore the new name for the Late Miocene species Brachylebias persicus Priem, 1908 is Aphanius persicus (Priem, 1908). In addition, he stated that a new name has to be assigned to the extant A. persicus (Jenkins, 1910). However, before a new species name can be assigned, it is necessary to demonstrate that the two species, currently named A. persicus, are different. Here we show that slight differences are present in the meristic characters between the fossil A. persicus (Priem, 1908) and the extant A. persicus (Jenkins, 1910), and that clear differences are present with regard to the size and morphology of the scales and also with regard to the shape of the jaw teeth. We demonstrate that the epithets blanfordii and pluristriatus, both introduced for Aphanius species by Jenkins (1910), do not represent alternative names, and we introduce A. farsicus as replacement name for A. persicus (Jenkins, 1910).